Assessment of the impact of multiple mild-steam decontaminations on the protection performance of disposable KN95 filtering facepiece respirators. Issue 2 (June 2021) - Zentgraf, F.; Johe, P.; Hoche, H.; Göckel, B.; Becker, S.; Oechsner, M.; Dreizler, A.
Summary: The COVID-19 pandemic caused tremendous supply bottlenecks of single-use filtering facepiece respirators (FFRs) leading to a growing need for a potential reuse. This study assesses the impact of multiple mild-steam decontaminations with 121 °C/2000 mbar/20 min on the protection performance of disposable FFRs. It focuses on FFRs of type KN95 that is recently dominating the markets, but its decontamination is not covered in the literature. It was found that up to ten cycles, only minor degradation in the filter efficiency, breathing resistance and none in the material structure is apparent, suggesting a potential for multiple decontamination cycles at almost unchanged protective properties of KN95 FFRs.